Evaluation of Regional Public Service Agency Policies on Tourism Service Businesses of State Vocational High Schools 27 Jakarta in 2022-2023 - Windy Calm; Achmad Lutfi (Publikasi Indonesia, 2024)
The Tourism Service Business is one of the business units managed in the production unit at BLUD SMKN 27 Jakarta which implements teaching factory-based learning. SMKN 27 Jakarta has implemented the BLUD policy in the management of production units since 2019. Based on the results of the policy eval_uation using the eval_uation criteria of effectiveness, efficiency, adequacy, equity, responsiveness and accuracy from William N. Dunn, the policy performance of the business units of the Student Service Business expertise group did not achieve its goals because the production capacity and development of service products in ULW did not run optimally and did not cover all expertise competencies. The management of BLUD SMKN 27 Jakarta as the driving force of institutional work needs to conduct a review to adjust the implementation of curricula that optimize the utilization of facilities and infrastructure in ULW business units for learning practices that can produce products and services that have a selling value according to the target market and business implementation must be operational and oriented, providing financial benefits for welfare and reinvestment for schools and, Developing a strategic plan for the development of school programs should include optimizing production capacity, competencies and expertise of students and teachers who must be involved in the production process.